2011
DOI: 10.1021/ma1026077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Filler Surface Modification on Large Scale Mechanics of Styrene Butadiene/Silica Rubber Composites

Abstract: |Macromolecules 2011, 44, 4366-4381 Macromolecules ARTICLE 2.6. Tensile Testing. Tensile tests were done with a material testing machine (Zwick 1456, Z010, Ulm, Germany) with a crosshead speed of 200 mm min À1 (ISO 527) using optical strain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
232
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(236 citation statements)
references
References 35 publications
4
232
0
Order By: Relevance
“…The earlier onset of nonlinearity has been previously attributed to the effect of strain amplification: the matrix experiences a higher local strain than the macroscopic strain due to the presence of the stiff nanotubes (Richter et al 2009;Costa et al 2008). This effect is generally enhanced by confinement of polymer chains located near the surface of a nanotube (Stöckelhuber et al 2011;Vilgis 2005). Since no specific surface modification of MWCNTs was performed in our materials, chemical interactions between the matrix and CNTs are likely to be weak.…”
Section: Resultsmentioning
confidence: 99%
“…The earlier onset of nonlinearity has been previously attributed to the effect of strain amplification: the matrix experiences a higher local strain than the macroscopic strain due to the presence of the stiff nanotubes (Richter et al 2009;Costa et al 2008). This effect is generally enhanced by confinement of polymer chains located near the surface of a nanotube (Stöckelhuber et al 2011;Vilgis 2005). Since no specific surface modification of MWCNTs was performed in our materials, chemical interactions between the matrix and CNTs are likely to be weak.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of elastomer-based nanocomposites, consisting of inorganic nanoparticles dispersed in the polymer matrix, depend drastically on the interactions between the polymer matrix and the nanofillers. 7,8 Different dynamic moduli can be obtained by tuning these interactions, which leads to the desired increase of mechanical reinforcement at low strain magnitudes. However, a significant loss of the composite's rigidity appears at higher strain magnitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The adjacent inclusions under deformation retain their relative position in the groups of small agglomerates. This contradicts the popular theory [6,7], according to which the most loaded part of the matrix is in the small gaps at the vicinity of polymer-filler interphase. Our experimental studies have shown that the more preferable scenario is the redistribution of the load over the relatively filler-free areas of the matrix than the moving apart of adjacent inclusions.…”
Section: Discussionmentioning
confidence: 66%
“…The surface of active filler in rubber matrix is covered by glassy-like layer of immobilized polymer chains [4,5]. According to theory [6][7][8], this layer gradually goes into matrix (the overall thickness of the modified polymer is ~10 nm). Some authors suppose, that being deformed, polymer in this layer is stretched and forms oriented strands [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation